2003
DOI: 10.1182/blood-2002-12-3834
|View full text |Cite
|
Sign up to set email alerts
|

Common lymphoid progenitors rapidly engraft and protect against lethal murine cytomegalovirus infection after hematopoietic stem cell transplantation

Abstract: Lymphoid deficiency after allogeneic hematopoietic cell transplantation (HCT) results in increased susceptibility to infection; however, transplantation of mature lymphocytes frequently results in a serious complication known as graft-versushost disease (GVHD). Here we demonstrate in mice that both congenic as well as allogeneic transplantation of low numbers of highly purified common lymphoid progenitors ( IntroductionMyeloablative doses of chemoradiation therapy used in preparation for hematopoietic cell tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 43 publications
1
49
0
Order By: Relevance
“…The cells are of particular interest to clinicians as a potential tool for the augmentation of immune reconstitution following stem cell transplantation [16,17]. Our patient may provide further corroborative evidence for the existence of the CLP in humans.…”
Section: Discussionsupporting
confidence: 63%
“…The cells are of particular interest to clinicians as a potential tool for the augmentation of immune reconstitution following stem cell transplantation [16,17]. Our patient may provide further corroborative evidence for the existence of the CLP in humans.…”
Section: Discussionsupporting
confidence: 63%
“…184 Similarly, murine lymphoid progenitor cells have also been shown to confer protection against infection, specifically CMV. 185 As these cells are derived from HSCs, further study of these progenitor cells and their immunomodulatory effects may reveal novel ways of HSC regulation and alternative approaches to their expansion.…”
Section: Cellular Factorsmentioning
confidence: 99%
“…For instance, studies using common lymphoid progenitors have shown that a rapid burst of lymphopoiesis can protect mice against lethal doses of cytomegalovirus after irradiation and HSC transplantation. 10 To test the ability of non-self-renewing progenitors to generate immunity in unconditioned immunocompromised recipients, we transplanted 180 c-kit+ lineage-Sca-1+ flk2+ (KLS flk2+) progenitor cells or 500 c-kit+ lineage-Sca-1+ CD34-flk2-HSCs into unconditioned recombinase activating gene 2 and interleukin-2 receptor common gamma chain-deficient (RAG2 -/-γc -/-) mice. 11 These KLS flk2+ cells retain myeloid and lymphocytic differentiation potential, but lack the ability to self-renew for the lifetime of the organism.…”
Section: Rapid Lymphopoiesis By Non-self-renewing Progenitorsmentioning
confidence: 99%